2020
DOI: 10.4081/ijfs.2020.8419
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aflatoxin M1 enrichment factor in different cow milk cheese hardness category

Abstract: Aflatoxin M1 (AFM1) is a hepatocarcinogenic and genotoxic derivative of aflatoxin B1 excreted into milk after ingestion of feed contaminated by Aspergillus genus fungi. Because of the important role of dairy products, especially cow cheese, in the human diet, there is great concern about the presence of AFM1 in this food category. EC Regulation No. 1881/2006 establishes the importance of the enrichment factor (EF), an essential parameter that must be defined in order to evaluate the maximum level of the toxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…the AMF1 enrichment factor in semi‐soft/semi‐hard cheeses, Primosale (Pecorelli et al . 2020), Caciotta (Pecorelli et al . 2019) and Pecorino (Pecorelli et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the AMF1 enrichment factor in semi‐soft/semi‐hard cheeses, Primosale (Pecorelli et al . 2020), Caciotta (Pecorelli et al . 2019) and Pecorino (Pecorelli et al .…”
Section: Discussionmentioning
confidence: 99%
“…The concentration factor of AFM1 has been reported to range from 2.5 to 3.3 in soft cheeses and from 3.9 to 5.8 in hard products (Yousef and Marth 1989). Accordingly, the Italian Ministry of Health has proposed provisional AFM1 enrichment factors of 5.5 and 3.0 for 'hard cheese' and 'soft cheese', respectively, where the 'hard cheese' includes the semi-hard, hard and very hard cheese categories, and the 'soft cheese' group consists of soft and semi-soft cheeses (Pecorelli et al 2020). However, a higher increase in the concentration of AFM1 in the final cheese over that in the milk has been reported for some soft products including Turkish white pickled cheese (Oruc et al 2006) (Pecorelli et al 2018), was shown to be about 4.1, 5.16 and 4.13, respectively.…”
Section: Cheese Hardnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed food consumption data were extrapolated from the latest version of the Comprehensive Food Consumption Database of the EFSA [ 25 ] on the basis of the 50th and 99th percentiles of Italian surveys of each population group: toddlers (≥12 months to <36 months old, weighing 11 kg), children (≥36 months to <10 years old, weighing 26 kg), adolescents (≥10 years to <18 years old, weighing 53 kg), adults (≥18 years to <65 years old, weighing 70 kg), and the elderly (≥65 years, weighing 70 kg). In order to define the contribution of dairy products to AFM1 human dietary exposure, for milk destined for use in cheesemaking, we took into consideration specific concentration factors with respect to the use of milk in a specific cheese category [ 26 ]. The cheese category was established followed the EU Decision of 18 December 1996 [ 17 ], which categorized cheeses by their moisture content on a fat-free basis (MFFB), identifying five different cheese categories: soft (MFFB ≥ 68%), semi-soft (68% > MFFB ≥ 62%), semi-hard (62% > MFFB ≥ 55%), hard (55% > MFFB ≥ 47%), and very hard (MFFB < 47%).…”
Section: Methodsmentioning
confidence: 99%
“…As far as potential hazards are Aflatoxin B1 as re-emerging contaminant Aflatoxin B1 contamination of feeds for dairy ruminants is re-emerging with climate changes (9,34) Presence of its metabolite Aflatoxin M1 in milk and dairy products Exposure to aflatoxin M1 may occur through milk, cheese and other dairy products, where the metabolite can concentrate as it is bound to the protein fraction of milk (32). The enrichment factors in diverse cheese types can be remarkably different and current regulatory limits may require updating (35) Risk analysis of aflatoxin M1 in milk and dairy products Aflatoxin M1 has similar toxicological characteristics as the parent compound. Legal limits for aflatoxin B1 in feeds and aflatoxin M1 in milk are established in the EU as a component of a farm-to-fork approach to prevent potential risks for consumers (32,33) Mode of action of mineral binders a to decrease aflatoxin bioavailability Based on physicochemical properties: negatively charged and with high surface area, pore volume, swelling ability, and high cation exchange capacity.…”
Section: Rbamentioning
confidence: 99%